2023
DOI: 10.3390/pathogens12020244
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2-Specific T Cell Responses in Immunocompromised Individuals with Cancer, HIV or Solid Organ Transplants

Abstract: Adaptive immune responses play an important role in the clinical course of SARS-CoV-2 infection. While evaluations of the virus-specific defense often focus on the humoral response, cellular immunity is crucial for the successful control of infection, with the early development of cytotoxic T cells being linked to efficient viral clearance. Vaccination against SARS-CoV-2 induces both CD4+ and CD8+ T cell responses and permits protection from severe COVID-19, including infection with the currently circulating v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 175 publications
2
18
0
Order By: Relevance
“…Costiniuk et al, in their study on HIV patients, found that anti-RBD and anti-S antibody levels were maintained in 92% patients after 6 months and in 100% patients after 1 month of third dose and suggested timely booster administration in HIV patients for improved immune response [ 23 ]. Studies have shown reduced seroconversion in immunocompromised patients [ 24 ]. Therefore, many European countries recommend booster (third) dose for immunocompromised individuals; even some countries advocate extended (forth dose) or yearly dose in susceptible and vulnerable population with different cut-off for age, citing the waning effect of vaccination over time [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Costiniuk et al, in their study on HIV patients, found that anti-RBD and anti-S antibody levels were maintained in 92% patients after 6 months and in 100% patients after 1 month of third dose and suggested timely booster administration in HIV patients for improved immune response [ 23 ]. Studies have shown reduced seroconversion in immunocompromised patients [ 24 ]. Therefore, many European countries recommend booster (third) dose for immunocompromised individuals; even some countries advocate extended (forth dose) or yearly dose in susceptible and vulnerable population with different cut-off for age, citing the waning effect of vaccination over time [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…have been associated with increased risk of fatal outcomes during acute Covid-19 [24]. However, the CD4 + /CD8 + T-cell ratio appears to remain constant during SARS-CoV-2 infection in PWH compared with HIV-uninfected individuals in whom the ratio is increased [25].…”
Section: T-cell Cross-reactivity To Omicronmentioning
confidence: 96%
“…A total of 24 HIV-uninfected women (n = 12 pregnant, n = 12 postpartum) and 15 WLWH (n = 5 pregnant n = 5 postpartum, n = 5 not pregnant) were recruited with a median age of 30 years (IQR: [22][23][24][25][26][27][28][29][30][31][32][33] and 34 years (IQR: 29-40; p = 0.035), respectively. Most of the participants (56.4%, 22/39) had been infected with the Beta variant (B.…”
Section: Characteristics Of Enrolled Participantsmentioning
confidence: 99%
“…Both CD4+ and CD8+ T cells are necessary for viral control. Accordingly, cellular or functional T-cell deficiencies are associated with severe COVID-19 disease courses ( 20 ). However, an uncontrolled activity of these cells can lead to inflammation in infected organs and subsequent severe pathologies.…”
Section: Introductionmentioning
confidence: 99%